BS EN ISO 22579. Infant formula and adult nutritionals. Determination of fructans. High performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) after enzymatic treatment. (18th December 2019) - British Standards Institution,
No abstract available